Analysis of the reliability value of building safety System (nkskb) and level of occupants readiness in facing Fire at johar market, semarang, central java (south johar) - Esterida, Berliana; Jaryati, Jaryati; Suwandi, Putri Anggi Permata; Rizani, Mohammad Debby (International Journal of Sustainable Building, Infrastructure and Environment (IJOSBIE), 2022)
Abstract. Public buildings are buildings used by people from various walks of life, which are built or intended not for the benefit of private residences, but for the general public which are identical to community service centers (Siti Azizah, 2013). One of the public buildings is the Johar market, Semarang. An important aspect of a public building is fire safety. The purpose of this study was to determine the level of reliability of the public building security system against fire hazards in the Johar Semarang market (Johar Selatan), and the readiness of the occupants of the Johar Semarang market building in the face of fire disasters. The method used in this research is descriptive-quantitative research method which is collecting data obtained from interviews, field notes, personal documentation, researcher notes, and other supporting documents. The results of the analysis of the utility component assessment of the four variables resulted in a Building Safety System Reliability Value (NKSKB) of 86.12%, based on these results it can be concluded that the reliability value of the building is in good and safe condition. The level of readiness of residents in facing the danger of fire disasters is still in the poor category with an average level of readiness of residents of 51.12%. This shows the need for increased application of protection systems and rescue facilities, especially for several protection systems that are still damaged and not functioning as well as socialization to residents regarding the use of fire extinguishers, fire simulations, and the need to provide adequate PPE.Keywords: Public Buildings, Level of Reliability, Occupancy Readiness